Audit Quality and Integrated Reporting on Firm Value: Analysis of the Moderating Role of GCG - Azizahtut Ta'zhiyah; Nur Fadjrih Asyik (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
This study analyses the effect of audit quality and the quality of integrated reporting on firm value, with Good Corporate Governance (GCG) as a moderating variable. Based on the agency theory and signalling theory, the study examines how the mechanisms of auditing (audit quality and governance) and reducing information asymmetry (through integrated reporting) can align the agent needs and principal to improve firm value and function as a positive signal for the market. The population consists of Property companies listed on the Indonesia Stock Exchange (IDX) during 2021-2024, with 23 companies (92 observation data) as samples. Furthermore, the data analysis technique used was multiple linear regression and Moderated Regression Analysis (MRA). As a result, it indicates that audit quality as well as quality of integrated reporting have a positive and significant effect on firm value. However, Good Corporate Governance does not moderate the effect of audit quality. It means the audit quality is strong enough as a mechanism of independent audit. In contrast, Good Corporate Governance has a positive and significant moderation for the relationship between the quality of integrated reporting and firm value. In other words, a strong GCG strengthens the credible signal that is delivered through integrated reports, so that it improves market value.